2007
DOI: 10.1007/s10038-007-0181-y
|View full text |Cite
|
Sign up to set email alerts
|

Oculocutaneous albinism type 2 (OCA2) with homozygous 2.7-kb deletion of the P gene and sickle cell disease in a Cameroonian family. Identification of a common TAG haplotype in the mutated P gene

Abstract: In this study, we report on a Cameroonian family from the Ewondo ethnic group, presenting with three oculocutaneous albinism type 2 (OCA2) patients homozygous for the 2.7-kb deletion of the P gene. In one of these patients OCA2 was associated with sickle cell anaemia and in two with the sickle cell trait. We took this opportunity to determine single nucleotide polymorphism (SNP) haplotypes within the P gene in this family in comparison with a group of 53 OCA2 patients homozygous for the same mutation and with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
3
6
0
Order By: Relevance
“…Consanguinity was frequent in our group, with 26% of patients in consanguineous families, which is similar to that in Africa [23][24][25] and higher than in European countries, that is, 5-6% [26]. Contrary to our results, another study performed in Bahia, Brazil, reported inbreeding rates similar to those in Europe, with a prevalence of 7.5% [19].…”
Section: Discussionsupporting
confidence: 67%
“…Consanguinity was frequent in our group, with 26% of patients in consanguineous families, which is similar to that in Africa [23][24][25] and higher than in European countries, that is, 5-6% [26]. Contrary to our results, another study performed in Bahia, Brazil, reported inbreeding rates similar to those in Europe, with a prevalence of 7.5% [19].…”
Section: Discussionsupporting
confidence: 67%
“…22 Oculocutaneous albinism type 2 is the commonest OCA in Africa and some mutations in the OCA2 locus have a clearly defined African origin. [23][24][25] However, due to the regular and historic immigration from Africa to Europe, OCA2 cases are not rare among Europeans, and, as such, OCA2 mutations are routinely detected in genetic studies on albinism conducted in European countries, although logically, with lower prevalence, as compared to Africa. [14][15][16] Oculocutaneous albinism type 3, associated with recessive mutations in the TYRP1 gene, is the less frequent type of OCA.…”
Section: Types Of Albinismmentioning
confidence: 99%
“…Eye abnormalities, the most important and handicapping traits for persons with albinism (besides the obvious hypopigmentation), include fovea hypoplasia, reduced pigmentation of retinal pigment epithelium cells, photoreceptor rod cell deficit, misrouting of the optic nerves at the chiasm, reduced pigmentation in the iris, photophobia and nystagmus . Several studies suggest that all known forms of albinism affect 1:17 000 newborns in Western societies, mostly North America and Europe, although frequencies ranging from 1:10 000–20 000 have been also reported and other prevalences apply in Asia . In some countries in Africa, due to consanguinity issues, the prevalence of albinism can be much higher …”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of all known forms of albinism in the best-studied Western populations, mostly in North America and Europe, appears to be 1:17 000 newborns (within a range of 1:10 000-20 000) (Gargiulo et al, 2011;Grønskov et al, 2007Grønskov et al, , 2009Hutton and Spritz, 2008a,b;King and Oetting, 2006;Oetting and King, 1999;Rooryck et al, 2008;Rundshagen et al, 2004;Z€ uhlke et al, 2007). Different frequencies of several types of albinism have been also reported from Asia (Inagaki et al, 2004;Lin et al, 2006;Suzuki and Tomita, 2008;Wei and Li, 2013;Wei et al, 2010Wei et al, , 2011, whereas the highest prevalence is found in some countries in Africa, mostly due to consanguinity issues and founder effects (Aquaron et al, 2007;Cruz-Inigo et al, 2011;Spritz et al, 1995) ( Figure 1).…”
Section: Introductionmentioning
confidence: 96%